Immobilization of lipase on poly(N-vinyl-2-pyrrolidone-co-styrene) hydrogel - Basri, M.; Harun, A.; Ahmad, M. B.; Razak, C. N. A.; Salleh, A. B. (Wiley, 2001)
Lipase from Candida rugosa was immobilized by entrapment while polymerizing a poly(N-vinyl-2-pyrrolidone-co-styrene) [poly(VP-co-ST)] hydrogel using ethylene dimethacrylate (EDMA) as the crosslinking agent. The immobilized enzymes were used in the esterification reaction of oleic acid and butanol in hexane. The activities of the immobilized enzymes and the leaching ability of the enzyme from the support with respect to the different compositions of the hydrogels were investigated. The thermal, solvent, and storage stability of the immobilized lipases were also determined. The activities were relatively higher when the percent compositions of VP(%): ST(%) were 50:50 and 30:70. The lipase immobilized on VP(%):ST(%) 50:50 showed the highest thermal stability, while lipase immobilized on VP(%):ST(%) 30:70 exhibited the highest solvent stability.